ADAPTASI SOSIAL-EKONOMI MASYARAKAT RUMAH LANTING SEBAGAI BENTUK KETAHANAN HIDUP DI BANTARAN SUNGAI KAHAYAN, PAHANDUT SEBERANG - Kamelia Simamora; Saputra Adiwijaya; Elia Damayanti (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The purpose of this study is to identify factors that influence adaptation and to analyze the socio-economic adaptation strategies of stilt house communities on the banks of the Kahayan River, Pahandut Seberang, Palangka Raya.This study conducted descriptive qualitative research with a case study in Pahandut Seberang. Data were collected through in-depth interviews, field observations, and documentation of seven key informants, namely heads of families who had lived in the area for at least five years. The results showed that economic factors and river-dependent occupations, such as fish cages, which require physical proximity, were the main reasons for choosing stilt houses. There are three main types of adaptation used. The first is physical adaptation, which includes independent drinking water treatment and floating stilt houses; the second is economic adaptation, which includes dual livelihood strategies, such as fishing and fish cages; and the last is social adaptation, which is created by enhancing mutual cooperation and solidarity among residents to overcome infrastructure limitations and environmental impacts. Overall, stilt house communities use socio-economic adaptation strategies to demonstrate local resilience to development pressures and environmental change. These findings are crucial in helping local governments develop more equitable, inclusive, and sustainable policies for riverside communities.